Paramedics' experiences of barriers to, and enablers of, responding to suspected or confirmed COVID-19 cases: a qualitative study - Ursula Howarth; Peta-Anne Zimmerman; Thea F. van de Mortel; Nigel Barr (BMC, 2024)
Abstract Background Paramedics' work, even pre-pandemic, can be confronting and dangerous. As pandemics add extra stressors, the study explored paramedics' lived experience of the barriers to, and enablers of, responding to suspected or confirmed Coronavirus Disease 2019 (COVID-19) cases. Methods This exploratory-descriptive qualitative study used semi-structured interviews to investigate Queensland metropolitan paramedics' experiences of responding to cases during the COVID-19 pandemic. Interview transcripts were analysed using thematic analysis. Registered Paramedics were recruited by criterion sampling of staff who experienced the COVID-19 pandemic as active officers. Results Nine registered paramedics participated. Five themes emerged: communication, fear and risk, work-related protective factors, leadership, and change. Unique barriers included impacts on effective communication due to the mobile nature of paramedicine, inconsistent policies/procedures between different healthcare facilities, dispatch of incorrect information to paramedics, assisting people to navigate the changing healthcare system, and wearing personal protective equipment in hot, humid environments. A lower perceived risk from COVID-19, and increased empathy after recovering from COVID-19 were unique enablers. Conclusions This study uncovered barriers and enablers to attending suspected or confirmed COVID-19 cases unique to paramedicine, often stemming from the mobile nature of prehospital care, and identifies the need for further research in paramedicine post-pandemic to better understand how paramedics can be supported during public health emergencies to ensure uninterrupted ambulance service delivery.